Penerapan Project Based Learning berbantuan Media Pembelajaran Digital Interaktif terhadap Hasil Belajar Siswa Kelas XI Akuntansi SMK Negeri 19 Jakarta - Salsa Bela Winafa Putri; Ati Sumiati; Achmad Fauzi (Qalam : Jurnal Ilmu Kependidikan, 2026)
This study aims to determine the effectiveness of implementing the Project-Based Learning (PjBL) model assisted by interactive digital learning media—namely Quizizz, Mentimeter, Canva, Google Spreadsheet, and Google Form on students' cognitive learning outcomes. The research methodology employed a Quasi-Experiment with a Non-Equivalent Control Group Design. The population comprised all Grade XI Financial Accounting students at SMK Negeri 19 Jakarta, with a final sample consisting of 35 students in the experimental group and 35 students in the control group. Data collection instruments included pre-tests and post-tests, which were analyzed using non-parametric statistical tests. The test results indicated a significant increase in learning outcomes from pre-test to post-test in both groups. However, comparative test results proved that the experimental class achieved a significantly higher competency attainment within the effective category, whereas the control class fell into the ineffective category. Furthermore, these findings offer an innovative reference for accounting teachers to deliver complex material interactively, while equipping students with authentic learning experiences that hone 21st-century skills and digital literacy in line with industry needs. For school stakeholders and the department of education, this study provides concrete data to replicate project-based teaching modules across other vocational subjects and to design professional development programs for teachers. Additionally, it offers positive implications for industry by narrowing the competency gap among vocational graduates and provides valid instruments and intervention procedures for future researchers. Conclusively, the implementation of the Project-Based Learning model assisted by interactive digital media is significantly more effective in accelerating students' cognitive accounting competencies compared to conventional methods.